Bioeconomy in Costa Rica: sociotechnical change and rural territorial development perspectives - Barboza Arias, Luis Miguel (Journal Studies of Public Policy, 2021)
The development of Science, Technology and Innovation (STI) has become an essential factor for the economic growth of a country. This article seeks to show the importance of public investment policies for STI in the conformation of the scientific field and in the professional trajectories of researchers assigned to the National System of Researchers (SNI) in area VIII-Engineering and Technological Development in Chiapas, an entity in the Southeast of Mexico. This is a documentary research that used selection and exclusion criteria, such as the temporality of the documents and the methodology used, to mention some of them, in order to obtain guiding documents and significant secondary sources that offered relevant information. The results revealed that the application of public policies for investment in STI is carried out unequally in the different entities of Mexico, which has caused Chiapas not to reach the desirable levels of development. It is concluded that public investment policies are relevant, since they have become the opportunity to acquire the necessary tools for researchers in Chiapas to continue developing their work.